TINGKAT KEBERHASILAN MOULTING DAN KELULUSAN HIDUP (SURVIVAL RATE) KEPITING BAKAU (Scylla serrata Forskal) DENGAN PERLAKUAN SALINITAS BERBEDA - Mohammad Sayuti; Iman Supriatna; Intannurfemi Hismayasari; I Gusti Ayu Budiadyani; Ahmad Yani; Vini Taru P; Hadi Nurohman; Saidin Saidin (Jurnal Airaha, 2018)
The existence of the provisions of the Ministry of Marine Affairs and Fisheries that the capture and / or expenditure of crabs (Scylla spp.) with the provisions of the size of the carap above 15 (fifteen) cm or weight above 200 (two hundred) grams per tail becomes a challenge in the soft carapas (soca) crab business that generally using crabs with an average weight below 150 grams. This study aims to determine the success rate of moulting and survival rate crab (Scylla serrata Forskal) with different salinity treatment using crabs weighing above 200 gr. This study used Completely Randomized Design with 5 (five) treatments and used 3 (three) replications, analysis of variance (ANOVA) at 95% confidence level was used to analyzing the data obtained. If there was a significant difference (P <0.05) then proceed with LSD test (Least Significant Differences) with 95% confidence level. The results of this research showed that the highest moulting success rate was obtained from the treatment with salinity of 10 ppt. While the highest survival rate (SR) was obtained from the treatment with salinity 30 ppt.